Empirical Study on the Difficulty of Enforcing Minor Children’s Alimony after Divorce - Zhu, Yue (International Journal of Social Sciences and Public Administration, 2024)
With the development of modernization, the concept of marriage and family in China is also changing, the divorce rate is on an amazing rise. In addition to the division of property, the raising of minor children is also the focus of divorce cases. This paper takes a district court of C City, S Province as a sample, and statistics the cases of alimony enforcement in this court from 2023.1.1 to 2023.8.31, and summarizes the characteristics of such cases. It is found that in judicial practice, there are blood parents’ antagonism and communication failure in the enforcement of alimony; lack of affection between parents who do not live together and their dependent children; the person subject to enforcement intentionally evades payment; the executee’s inability to pay and many other problems. And try to put forward the solution path, such as multi-party interaction to ease the contradiction; interpretation of the law to protect parental rights; strengthen the penalty of refusing to enforce the establishment of a unified deduction network; explore the implementation of compulsory insurance system for minors in order to provide reference for the case of child maintenance enforcement in China.